Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202580023410.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2025-03-17
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]根据作为本公开的一个方式的非水电解质二次电池,能够在为高容量的同时减小电池电阻。
Smart Images

Figure CN122996527A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to non-aqueous electrolyte secondary batteries, and more particularly to low-resistance non-aqueous electrolyte secondary batteries. Background Technology
[0002] Previously, non-aqueous electrolyte secondary batteries, which are high-output, high-capacity rechargeable batteries, have been widely used. They consist of a positive electrode, a negative electrode, and a non-aqueous electrolyte, allowing Li ions to move between the positive and negative electrodes for charging and discharging. Patent Document 1 discloses a technique for reducing the resistance of non-aqueous electrolyte secondary batteries by forming a carbonaceous coating on the surface of a lithium transition metal composite oxide, which serves as the positive electrode active material.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: International Publication No. 2023 / 203952 Summary of the Invention
[0006] In recent years, there has been an increasing demand for higher output and higher capacity in non-aqueous electrolyte secondary batteries. The inventors have conducted in-depth research and discovered that by forming a carbonaceous coating on the surface of the positive electrode active material and by including a negative electrode active material and a silicate compound in the negative electrode mixture layer, wherein the negative electrode active material contains silicon-containing materials, a specific reduction in resistance during charging can be achieved compared to existing technologies such as those described in Patent Document 1.
[0007] The purpose of this disclosure is to provide a high-capacity, low-resistance non-aqueous electrolyte secondary battery.
[0008] The non-aqueous electrolyte secondary battery, as one embodiment of this disclosure, is characterized by comprising: an electrode body including a positive electrode and a negative electrode, and a non-aqueous electrolyte, having: a positive current collector and a positive electrode flux layer formed on the surface of the positive current collector; the negative electrode having: a negative current collector and a negative electrode flux layer formed on the surface of the negative current collector; the positive electrode flux layer comprising a positive active material; a carbonaceous coating formed on the surface of the positive active material; the carbonaceous coating containing one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li; and the negative electrode flux layer comprising a negative active material and a silicate compound, wherein the negative active material comprises a silicon-containing material.
[0009] According to the non-aqueous electrolyte secondary battery as one aspect of this disclosure, it is possible to reduce battery resistance while achieving high capacity. Attached Figure Description
[0010] Figure 1 This is an axial cross-sectional view of a non-aqueous electrolyte secondary battery, which is one example of an implementation method.
[0011] Figure 2 This is a schematic diagram of montmorillonite, an example of a silicate compound. Detailed Implementation
[0012] In recent years, there has been an increasing demand for higher output and higher capacity in non-aqueous electrolyte secondary batteries. Patent Document 1 discloses a technique for reducing resistance by modifying the positive electrode active material, but the required characteristics of non-aqueous electrolyte secondary batteries are becoming increasingly demanding, necessitating further technological innovation. The inventors have conducted in-depth research and discovered that by modifying both the positive and negative electrodes, both high capacity and high output can be achieved. Specifically, the inventors found that by forming a carbonaceous coating containing one or more elements selected from the group consisting of alkali metals and alkaline earth metals (excluding Li) on the surface of the positive electrode active material, and by including a negative electrode active material and a silicate compound in the negative electrode compound layer, wherein the negative electrode active material contains silicon-containing materials, a specific reduction in resistance during charging can be achieved compared to existing technologies. According to the inventors' research, the reduction in resistance when both the positive and negative electrodes are modified is greater than the simple sum of the reduction in resistance when only the positive electrode is modified and the reduction in resistance when only the negative electrode is modified.
[0013] The following is a detailed description of an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed herein. The example shown is a cylindrical battery in which wound electrode bodies are housed in a cylindrical outer casing. However, the electrode bodies are not limited to a wound type; they can also be a stacked type, where multiple positive and multiple negative electrodes are alternately stacked one by one with separators. Furthermore, the outer casing is not limited to a cylindrical shape; for example, it can be square, coin-shaped, or a battery casing made of laminates containing metal and resin layers.
[0014] Figure 1 This is an axial cross-sectional view of a cylindrical secondary battery 10 as an example of an implementation method. (See attached image.) Figure 1 As shown, the secondary battery 10 includes a wound electrode body 14, an electrolyte, and an outer casing 16 for housing the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound into a spiral shape with the separator 13 sandwiched between them. The outer casing 16 is a bottomed cylindrical metal container with an opening on one axial side, and the opening of the outer casing 16 is sealed by a sealing body 17. Hereinafter, for ease of explanation, the sealing body 17 side of the battery is referred to as the upper side, and the bottom side of the outer casing 16 is referred to as the lower side.
[0015] The positive electrode 11, negative electrode 12, and separator 13 constituting the electrode body 14 are all rectangular strips, which are alternately stacked radially in the electrode body 14 by being wound into a spiral shape in the length direction. The separator 13 isolates the positive electrode 11 and the negative electrode 12 from each other. To prevent lithium deposition, the negative electrode 12 is formed to be one size larger than the positive electrode 11. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in both the length and width directions. The two separators 13 are formed to be at least one size larger than the positive electrode 11, for example, by sandwiching the positive electrode 11. The electrode body 14 includes a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like. In the electrode body 14, the length direction of the positive electrode 11 and the negative electrode 12 is the winding direction, and the width direction of the positive electrode 11 and the negative electrode 12 is the axial direction. That is, the end faces of the positive electrode 11 and the negative electrode 12 in the width direction form the axial end faces of the electrode body 14.
[0016] Insulating plates 18 and 19 are respectively disposed above and below the electrode body 14. Figure 1 In the example shown, the positive lead 20 extends to the sealing body 17 through the through hole in the insulating plate 18, and the negative lead 21 extends to the bottom side of the outer casing 16 through the outer side of the insulating plate 19. The positive lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate, i.e., the cover 27, of the sealing body 17, which is electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative lead 21 is connected to the bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 becomes the negative terminal.
[0017] A gasket 28 is provided between the outer casing 16 and the sealing body 17 to ensure the airtightness of the battery interior. A groove 22 is formed in the outer casing 16, a portion of which protrudes inward and supports the sealing body 17. The groove 22 is preferably formed in a ring shape along the circumferential direction of the outer casing 16, and its upper surface supports the sealing body 17. The sealing body 17 is fixed to the upper part of the outer casing 16 by the groove 22 and the open end of the outer casing 16 that fits relative to the sealing body 17.
[0018] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27 are stacked sequentially from the electrode body 14 side, and it functions as a safety valve. Each component constituting the sealing body 17 has, for example, a circular or annular shape, and all components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected through their respective central portions, and the insulating member 25 is located between the peripheral portions. When the internal pressure of the battery rises due to abnormal heating, the lower valve body 24 deforms and breaks by pushing the upper valve body 26 upwards towards the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.
[0019] The following is a detailed description of the positive electrode 11, negative electrode 12, separator 13 and non-aqueous electrolyte constituting the secondary battery 10, especially the positive electrode 11 and negative electrode 12.
[0020] [positive electrode]
[0021] The positive electrode 11 has a positive current collector and a positive electrode flux layer formed on the surface of the positive current collector. The positive electrode flux layer is preferably formed on both sides of the positive current collector. For the positive current collector, a metal foil stable within the potential range of the positive electrode 11, such as aluminum or an aluminum alloy, or a thin film formed by depositing this metal on the surface, can be used. The thickness of the positive current collector is, for example, 10 μm or more and 30 μm or less.
[0022] The positive electrode binder layer includes, for example, a positive electrode active material, a conductive agent, and a binder. The thickness of the positive electrode binder layer is, for example, 10 μm or more and 150 μm or less on one side of the positive electrode current collector. The positive electrode 11 can be manufactured, for example, by coating the surface of the positive electrode current collector with a positive electrode binder slurry containing a positive electrode active material, a conductive agent, etc., allowing the coating to dry, and then calendering it to form positive electrode binder layers on both sides of the positive electrode current collector.
[0023] The preferred unit area weight of the positive electrode mixture layer is 280 g / m². 2 The above is further preferred to be 300g / m 2 The above explains how high battery capacity can be achieved. However, increasing the weight per unit area of the positive electrode flux layer results in a thicker layer, which can easily lead to uneven charging and discharging along the thickness direction, resulting in a tendency for reduced charge-discharge cycle characteristics. This reduction is particularly pronounced when the negative electrode flux layer contains a large amount of negative electrode active material, and this active material contains silicon-containing materials.
[0024] In this embodiment, as described above, a carbonaceous coating containing one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li is formed on the surface of the positive electrode active material, and the negative electrode additive layer contains a negative electrode active material and a silicate compound, wherein the negative electrode active material comprises a silicon-containing material. That is, when a carbonaceous coating containing one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li is formed on the surface of the positive electrode active material, and a silicate compound is included in the negative electrode additive layer, the diffusion of the non-aqueous electrolyte within the positive electrode additive layer can be ensured even if the weight per unit area of the positive electrode additive layer is increased. As a result, high battery capacity can be achieved while ensuring charge-discharge cycle characteristics. The upper limit of the weight per unit area of the positive electrode additive layer is, for example, 380 g / m². 2 .
[0025] It should be noted that the weight per unit area of the positive electrode mixture layer refers to the weight per unit area (unit: m²) of the positive electrode current collector in the region where the positive electrode mixture layer is formed. 2 The amount of positive electrode flux layer formed (unit: g). Specifically, when the positive electrode flux layer is formed equally on both sides of the positive electrode current collector, the weight per unit area of the positive electrode flux layer is calculated by dividing the mass of the positive electrode flux layer formed on one side of the positive electrode current collector by the area of the portion of the positive electrode current collector on that side where the positive electrode flux layer is formed. Furthermore, when the positive electrode flux layer is not formed equally on both sides of the positive electrode current collector, the weight per unit area of the positive electrode flux layer is calculated for each side in the same manner as described above. In this case, the weight per unit area of the positive electrode flux layer on any side is preferably 280 g / m². 2 The above is further preferred to be 300g / m 2 That's all. Furthermore, when the positive electrode flux layer is formed only on one side of the positive current collector, the weight per unit area of the positive electrode flux layer is calculated by dividing the mass of the positive electrode flux layer formed on one side of the positive current collector by the area of the portion on that side of the positive current collector where the positive electrode flux layer is formed. It should be noted that in the positive current collector, if there are exposed portions of the current collector where no positive electrode flux layer is formed, the area of these exposed portions is not included in the "region where the positive electrode flux layer is formed" in the calculation of the weight per unit area of the positive electrode flux layer.
[0026] Examples of conductive agents included in the positive electrode mixture layer include acetylene black (AB), carbon black (CB) such as Ketjen black, carbon nanotubes (CNT), graphene, graphite, and other carbon-based particles. These can be used individually or in combination of two or more. The content of the conductive agent in the positive electrode mixture layer relative to the total mass of the positive electrode mixture layer is, for example, 0.1% by mass or more and 10% by mass or less.
[0027] Examples of binders included in the positive electrode binder layer include fluorinated resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide resins, acrylic resins, polyolefin resins, and polyacrylonitrile (PAN). These can be used individually or in combination of two or more. The binder content in the positive electrode binder layer is, for example, 0.1% by mass or more and 10% by mass or less relative to the total mass of the positive electrode binder layer.
[0028] The positive electrode active material includes, for example, secondary particles formed by the aggregation of primary particles. The particle size of the primary particles constituting the secondary particles of the positive electrode active material is, for example, 0.02 μm to 2 μm. The particle size of the primary particles is determined as the diameter of the circumcircle in a particle image observed by a scanning electron microscope (SEM). The average particle size of the secondary particles of the positive electrode active material is, for example, 2 μm to 30 μm. Here, the average particle size refers to the median particle size (D50) on a volume basis. D50 refers to the particle size at which the cumulative frequency in the volume-based particle size distribution reaches 50% from the smallest end, also known as the median diameter. The particle size distribution of the secondary particles of the positive electrode active material can be measured using a laser diffraction-type particle size distribution measuring device (e.g., MicrotracBEL Co., Ltd., MT3000II) with water as the dispersion medium.
[0029] The positive electrode active material contained in the positive electrode additive layer may include, for example, a lithium transition metal composite oxide. The lithium transition metal composite oxide may be, for example, of the general formula Li... a Ni x M1 y M2 z O 2-b (Where, 0.8≤a≤1.2, 0.50≤x≤0.95, 0≤y<0.50, 0≤z≤0.05, 0≤b≤0.05, x+y+z=1, M1 is at least one element selected from the group consisting of Co, Mn, and Al, and M2 is at least one element selected from the group consisting of W, Nb, Ti, Zr, B, Sb, Si, Fe, Mo, Sn, Ca, Sr, and Bi) is shown in the composite oxide. The proportion of metal elements contained in the lithium transition metal composite oxide can be determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), electron beam microscopy (EPMA), etc.
[0030] Lithium transition metal composite oxides, for example, possess layered rock salt structures belonging to space group R-3m or space group C2 / m. Considering high capacity and crystal structure stability, lithium transition metal composite oxides preferably have a layered rock salt structure belonging to space group R-3m. The layered rock salt structure of lithium transition metal composite oxides can include a transition metal layer, a Li layer, and an oxygen layer. The charge and discharge reactions of the battery occur through the reversible movement of Li ions present in the Li layer.
[0031] A carbonaceous coating containing one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li is formed on the surface of the positive electrode active material. By forming a carbonaceous coating on the surface of the positive electrode active material, and containing a negative electrode active material and a silicate compound in the negative electrode mixture layer, wherein the negative electrode active material includes silicon-containing materials described later, the resistance of the non-aqueous electrolyte secondary battery can be specifically reduced. Here, the surface of the positive electrode active material refers to the surface of the secondary particles of the positive electrode active material. That is, the carbonaceous coating exists on the surface of the secondary particles of the positive electrode active material. The carbonaceous coating may exist in a dotted manner, covering at least a portion of the surface of the secondary particles of the positive electrode active material, or it may exist in a manner covering the entire surface of the secondary particles. It should be noted that the carbonaceous coating may exist at the interface where the primary particles of the positive electrode active material are in contact with each other.
[0032] As described above, the carbonaceous coating contains one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li, preferably at least one of Na and K. Furthermore, the carbonaceous coating may also contain S. It should be noted that the carbonaceous coating may contain Li. The presence of S in the carbonaceous coating can be confirmed by energy-dispersive X-ray spectroscopy (TEM-EDX). The presence of alkali metals such as Na and K, and alkaline earth metals in the carbonaceous coating can be confirmed by X-ray photoelectron spectroscopy (XPS).
[0033] The thickness of the carbonaceous coating is, for example, less than 30 nm. The lower limit of the thickness of the carbonaceous coating is, for example, 1 nm. The thickness of the carbonaceous coating is determined, for example, by an image of the cross-section of the positive electrode active material observed by transmission electron microscopy (TEM).
[0034] The cathode additive layer may contain a cathode active material without a carbonaceous coating on its surface. For example, the cathode additive layer may contain a lithium transition metal composite oxide without a carbonaceous coating on its surface. In the cathode additive layer, the proportion of cathode active material with a carbonaceous coating on its surface is preferably 90% by mass or more, and more preferably 99% by mass or more, relative to the total mass of the cathode active material.
[0035] Next, an example of a method for manufacturing a positive electrode active material with a carbonaceous coating formed on its surface will be described.
[0036] Carbonaceous coatings are formed, for example, in the following manner.
[0037] (1) Dissolve anionic surfactants in water to prepare aqueous solutions.
[0038] (2) Add lithium transition metal composite oxide powder as positive electrode active material to the above aqueous solution, stir, and adjust the suspension of lithium transition metal composite oxide dispersed in the aqueous solution.
[0039] (3) By calcining the residue obtained by filtering the above suspension, a positive electrode active material with a carbonaceous coating on its surface is obtained.
[0040] Anionic surfactants adsorb onto the surface of lithium transition metal complex oxides in water, forming a substantially uniform carbonaceous coating. As a surfactant, there are no particular limitations as long as it contains carbon (C) and one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li. The surfactant preferably contains at least one of Na and K. Furthermore, the surfactant may also contain sulfur (S). Examples of surfactants include sodium lauryl sulfate and potassium lauryl sulfate. The concentration of the surfactant in the aqueous solution is, for example, 0.1% to 10% by mass.
[0041] [negative electrode]
[0042] The negative electrode 12 has a negative electrode current collector and a negative electrode flux layer formed on the surface of the negative electrode current collector. The negative electrode flux layer is preferably formed on both sides of the negative electrode current collector. The negative electrode current collector can be a foil of a metal stable within the potential range of the negative electrode 12, such as copper or a copper alloy, or a thin film of the metal disposed on its surface. The thickness of the negative electrode current collector is, for example, 5 μm or more and 30 μm or less.
[0043] The negative electrode flux layer comprises a negative electrode active material and a silicate compound. The thickness of the negative electrode flux layer is, for example, 10 μm or more and 150 μm or less on one side of the negative electrode current collector.
[0044] Negative electrode active materials may include carbon materials and silicon-containing materials. Carbon materials may include, for example, graphite. Graphite can be any of the following: natural graphite such as flake graphite, block graphite, and amorphous graphite; artificial graphite such as block graphite; and artificial graphite such as graphitized mesophase carbon microspheres. Compared to carbon materials such as graphite, silicon-containing materials can absorb and store more lithium ions per unit mass. Therefore, by using silicon-containing materials in the negative electrode active material, high battery capacity can be achieved.
[0045] The silicon-containing material included in the negative electrode additive layer can be any material containing silicon. Examples include silicon alloys, silicon compounds, and silicon-containing composite materials, with silicon-containing composite materials being preferred. The median particle size (D50) of the composite material in terms of volume is typically smaller than that of the carbon material in terms of volume. The median particle size (D50) of the composite material in terms of volume is, for example, 1 μm or more and 15 μm or less. It should be noted that a single silicon-containing material can be used, or two or more materials can be used in combination.
[0046] The preferred silicon-containing material is a composite particle comprising an ion-conductive phase and a silicon phase dispersed in the ion-conductive phase. The silicon phase is formed by elemental silicon dispersed in a fine particulate form. In addition, the composite particle may be provided with a conductive layer covering a part of the surface of the ion-conductive phase. The conductive layer is made of a material having higher conductivity than the ion-conductive phase, and forms a good conductive path in the negative electrode mixture layer. The conductive layer includes, for example, conductive carbon, and covers 30% or more and 70% or less of the surface area of the ion-conductive phase. It should be noted that the coverage of the conductive layer can be calculated by, for example, X-ray photoelectron spectroscopy (XPS).
[0047] The ion-conductive phase is a continuous phase composed of an aggregate of finer particles than the aforementioned silicon phase. The ion-conductive phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase. The silicide phase is a phase of a compound containing Si and an element that is more electropositive than Si, and examples thereof include NiSi, Mg₂Si, TiSi₂, and the like.
[0048] From the viewpoint of high lithium ion conductivity and the like, the silicate phase preferably contains at least one element selected from lithium, sodium, potassium, rubidium, cesium, francium, beryllium, magnesium, calcium, strontium, barium, and radium. Among them, from the viewpoint of high lithium ion conductivity and the like, the silicate phase is preferably a lithium-containing silicate phase (hereinafter, sometimes referred to as a lithium silicate phase).
[0049] The lithium silicate phase is represented by, for example, the formula: Li 2z SiO 2+z (0<z<2). From the viewpoints of stability, ease of production, lithium ion conductivity and the like, z preferably satisfies the relationship of 0<z<1, and more preferably z=1 / 2.
[0050] In addition, another example of the preferred silicon-containing material is a composite particle having a sea-island structure in which fine silicon phases are substantially uniformly dispersed in an amorphous silicon oxide phase, and the whole is represented by the general formula SiO x (0<x≤2). The main component of the silicon oxide may be silicon dioxide. The content ratio (x) of oxygen element to silicon element is, for example, 0.5≤x<2.0, preferably 0.8≤x≤1.5.
[0051] Another preferred example of a silicon-containing material is a composite particle with an island structure in which a fine silicon phase is substantially uniformly dispersed in a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may contain crystalline phase components, but a predominance of amorphous phase components is preferred. The amorphous carbon phase, for example, is composed of carbon material with an average plane spacing of more than 0.34 nm for the (002) planes as determined by X-ray diffraction. The amorphous carbon phase, for example, is composed of amorphous carbon particles. It should be noted that when the silicon-containing material is a composite particle with an island structure in which a fine silicon phase is substantially uniformly dispersed in a carbon phase, the total mass of silicon element contained in the silicon-containing material can be consistent with the mass of the silicon phase.
[0052] The mass ratio of the silicon phase to the total mass of the silicon-containing material is preferably 30% by mass or more. In this case, the discharge capacity increases, and the battery easily achieves high output. Furthermore, the mass ratio of the silicon phase to the total mass of the silicon-containing material is preferably 60% by mass or less. At this point, the volume change of the negative electrode binder layer during charging and discharging can be reduced, the expansion and contraction of the electrode body 14 during charging and discharging can be suppressed, and the battery's durability easily becomes excellent. Therefore, the mass ratio of the silicon phase to the total mass of the silicon-containing material is preferably 30% by mass or more and 60% by mass or less.
[0053] The crystallite size of the silicon phase constituting the above composite particles is, for example, 10 nm or more and 30 nm or less. The crystallite size of the silicon phase is calculated by the Scherer formula from the half-width of the analytical peaks assigned to the Si(111) plane of the X-ray diffraction pattern of the silicon phase.
[0054] The ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode flux layer is preferably 20% by mass or more. This increases the discharge capacity of the negative electrode flux layer, achieving higher battery capacity.
[0055] Furthermore, the ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode binder layer is preferably 50% by mass or less, more preferably 40% by mass or less. If the ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode binder layer exceeds 50% by mass, the volume change of the negative electrode binder layer during charging and discharging becomes excessive, and sometimes the diffusivity of the non-aqueous electrolyte within the electrode body 14 decreases. Therefore, the ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode binder layer is preferably 20% by mass or more and 50% by mass or less, more preferably 20% by mass or more and 40% by mass or less. It should be noted that the mass of silicon can be the same as the mass of the silicon phase. That is, the ratio of the mass of the silicon phase to the mass of the negative electrode binder layer can be 20% by mass or more and 50% by mass or less.
[0056] The total mass of silicon in silicon-containing materials can be determined using ICP (Inductively Coupled Plasma). ICP is a method in emission spectroscopy. When energy is applied to the plasma from an external source to the sample being analyzed, the constituent elements (atoms) are excited.
[0057] The silicate compounds contained in the negative electrode binder layer exhibit lithium affinity and high lithium diffusion capacity. These silicate compounds include layered silicate minerals, such as layered silicate minerals. Layered silicate minerals consist of a structure composed of multiple stacked silicate layers. Layered silicate minerals can be, for example, granular. Examples of layered silicate minerals include plate-like particles, spherical particles, blocky particles, and rod-shaped particles. A typical example of a layered silicate mineral is montmorillonite (MMT). Layered silicate minerals such as montmorillonite possess water swelling properties, cation adsorption capacity, and cation diffusion capacity.
[0058] Figure 2 This is a schematic diagram of montmorillonite, a silicate compound contained in the negative electrode. Montmorillonite has a composition of (Na, Ca). 0.33 (Al,Mg)x(Si4O 10 The composition represented by )(OH)2·nH2O.
[0059] Specifically, montmorillonite constitutes the basic layer 30 of the layered structure. Within this basic layer 30, two-dimensional tetrahedral layers 31 (formed by the two-dimensional bonding of Si and O) and two-dimensional octahedral layers 32 (formed by the two-dimensional bonding of Al and OH) share a portion of O ions. An octahedral layer 32 is symmetrically sandwiched between two tetrahedral layers 31. Montmorillonite expands the interlayer by allowing water molecules to enter between the two basic layers 30. Additionally, Na+ is formed between the two basic layers 30. + Ca 2+ K + A layer of exchangeable cations. Therefore, silicate compounds containing montmorillonite exhibit high adsorption capacity for lithium ions, which are cations. Furthermore, it is known that the energy consumption for lithium ion diffusion within the crystal is reduced in silicate compounds. Therefore, silicate compounds are considered to possess high lithium ion diffusivity.
[0060] The layered silicate compound is preferably at least one smectite. Preferred smectites, besides montmorillonite mentioned above, include halloysite, lithium montmorillonite, bedesulfurite, chlorodiatomite, soapstone, and zinc montmorillonite. Among the layered silicate compounds, smectite has a high affinity for lithium ions, thus more effectively improving the lithium ion diffusion of the negative electrode mixture layer. The negative electrode mixture layer may contain, for example, at least one smectite selected from the group consisting of montmorillonite, halloysite, lithium montmorillonite, bedesulfurite, chlorodiatomite, soapstone, and zinc montmorillonite. Montmorillonite is preferred.
[0061] The negative electrode binder layer may also contain a binder. Examples of binders included in the negative electrode binder layer include: styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts (such as PAA-Na, PAA-K, etc., and some neutralized salts), polyvinyl alcohol (PVA), etc. These can be used individually or in combination of two or more.
[0062] The negative electrode 12 can be manufactured, for example, by coating the surface of the negative electrode current collector with a negative electrode mixture slurry containing negative electrode active material, silicate compound, binder, etc., allowing the coating to dry, and then calendering to form a negative electrode mixture layer on both sides of the negative electrode current collector.
[0063] [Separator]
[0064] For the separator 13, a porous sheet with ion permeability and insulation properties can be used, for example. Specific examples of porous sheets include microporous films, woven fabrics, and nonwoven fabrics. The preferred material for the separator is polyolefins such as polyethylene and polypropylene, or cellulose. The separator 13 can be a laminate containing a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. Alternatively, it can be a multilayer separator containing a polyethylene layer and a polypropylene layer, or a separator made by coating the surface of the separator 13 with a material such as an aramid resin or ceramic.
[0065] [Non-aqueous electrolytes]
[0066] Non-aqueous electrolytes, for example, have lithium-ion conductivity. Non-aqueous electrolytes can be liquid electrolytes (electrolytes) or solid electrolytes.
[0067] Liquid electrolytes (electrolytes) may include, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixtures of two or more of these solvents. The non-aqueous solvent may contain a halogen-substituted form, in which at least a portion of the hydrogen atoms of the solvent are replaced by halogen atoms such as fluorine. Examples of halogen-substituted forms include fluorocyclic carbonates such as fluoroethylene carbonate (FEC), fluorochain carbonates, and fluorochain carboxylic acid esters such as methyl fluoropropionate (FMP).
[0068] Examples of the aforementioned esters include: cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylic acid esters such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); and chain carboxylic acid esters such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP).
[0069] Examples of the aforementioned ethers include: 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-epoxybutane, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-eucalyptol, crown ethers and other cyclic ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, and dihexyl ether. Ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and other chain ethers.
[0070] The preferred electrolyte salt is a lithium salt. Examples of lithium salts include: LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, and LiB. 10 Cl 10Examples of lithium salts include lower aliphatic carboxylic acids such as lithium Cl, LiBr, LiI, phosphates, borates, and imide salts. Examples of phosphates include lithium difluorophosphate (LiPO₂F₂), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium tetrafluoro(oxalate)phosphate. Examples of borates include lithium bis(oxalate)borate (LiBOB) and lithium difluoro(oxalate)borate (LiDFOB). Examples of imide salts include lithium difluorosulfonylimide (LiN(FSO₂)₂), lithium difluoromethanesulfonylimide (LiN(CF₃SO₂)₂), lithium (trifluoromethanesulfonyl)(nonafluorobutanesulfonyl)imide (LiN(CF₃SO₂)(C₄F₉SO₂)), and lithium dipentafluoroethanesulfonylimide (LiN(C₂F₅SO₂)₂). Among these, LiPF₆ is preferred from the perspectives of ionic conductivity and electrochemical stability. The concentration of lithium salt can be, for example, less than 4 moles per 1 L of non-aqueous solvent, less than 3 moles, preferably less than 1.8 moles, more preferably more than 0.8 moles and less than 1.8 moles.
[0071] Non-aqueous electrolytes may contain additives. Examples of additives include unsaturated carbonates, acid anhydrides, phenolic compounds, benzene compounds, nitrile compounds, isocyanate compounds, sulpholactone compounds, sulfuric acid compounds, borate ester compounds, phosphate ester compounds, and phosphite ester compounds.
[0072] Examples of unsaturated cyclic carbonates include: vinylene carbonate, 4-methylvinylene carbonate, 4,5-dimethylvinylene carbonate, 4-ethylvinylene carbonate, 4,5-diethylvinylene carbonate, 4-propylvinylene carbonate, 4,5-dipropylvinylene carbonate, 4-phenylvinylene carbonate, 4,5-diphenylvinylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, etc. Unsaturated cyclic carbonates can be used alone or in combination of two or more. A portion of the hydrogen atoms in an unsaturated cyclic carbonate can be replaced by fluorine atoms. An anhydride can be an anhydrous product formed by the intermolecular condensation of multiple carboxylic acid molecules, preferably an anhydride of a polycarboxylic acid. Examples of anhydrides of polycarboxylic acids include: succinic anhydride, maleic anhydride, phthalic anhydride, etc.
[0073] Examples of phenolic compounds include phenol and hydroxytoluene. Examples of benzene compounds include fluorobenzene, hexafluorobenzene, and cyclohexylbenzene (CHB).
[0074] Examples of nitrile compounds include adiponitrile, heptanonitrile, propionitrile, and succinic anionylene. Examples of isocyanate compounds include methyl isocyanate (MIC), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and methylcyclohexane diisocyanate (BIMCH). Examples of sulcolone compounds include propane sulcolone and propenyl sulcolone. Examples of sulfuric acid compounds include ethylene sulfate, ethylene sulfite, dimethyl sulfate, and lithium fluorosulfate. Examples of borate compounds include trimethyl borate and tris(trimethylsilyl)borate. Examples of phosphate compounds include trimethyl phosphate and tris(trimethylsilyl) phosphate. Examples of phosphite compounds include trimethyl phosphite and tris(trimethylsilyl) phosphite.
[0075] As a solid electrolyte, examples include solid or gel-like polymer electrolytes and inorganic solid electrolytes. As an inorganic solid electrolyte, materials known in all-solid-state lithium-ion secondary batteries (e.g., oxide-based solid electrolytes, sulfide-based solid electrolytes, halogen-based solid electrolytes, etc.) can be used. Polymer electrolytes may contain, for example, lithium salts and a matrix polymer, or non-aqueous solvents, lithium salts, and a matrix polymer. As a matrix polymer, for example, a polymer material that gels by absorbing non-aqueous solvents is used. Examples of polymer materials include fluoropolymers, acrylic resins, and polyether resins.
[0076] Example
[0077] The present disclosure is further illustrated below by way of examples and comparative examples, but the present disclosure is not limited to the following examples.
[0078] <Experimental Battery Unit A>
[0079] [Preparation of positive electrode active material]
[0080] Sodium lauryl sulfate, used as a surfactant, was dissolved in water to prepare a 10% (w / w) aqueous solution. A LiNi alloy with a median particle size (D50) of 17 μm was then added to this aqueous solution. 0.8 Mn 0.2A lithium transition metal composite oxide of O2 was stirred for 5 minutes to adjust the concentration to 1200 g / L. The residue obtained by filtering the suspension was vacuum dried at 180 °C for 2 hours to obtain the positive electrode active material of Example 1. Based on the observation results of transmission electron microscopy (TEM), the thickness of the carbonaceous coating was 10 nm. Based on the observation results of energy dispersive X-ray spectroscopy (TEM-EDX), a peak originating from S was observed near 2.2 keV, confirming the presence of S in the carbonaceous coating. Furthermore, based on the analysis results of X-ray photoelectron spectroscopy (XPS), the presence of Na in the carbonaceous coating was confirmed.
[0081] [The production of the positive electrode]
[0082] A positive electrode active material, acetylene black, and polyvinylidene fluoride (PVDF) were mixed in a solid component mass ratio of 98:1:1, with an appropriate amount of N-methyl-2-pyrrolidone (NMP) added to prepare a positive electrode slurry. This positive electrode slurry was coated onto both sides of a positive electrode current collector formed from aluminum foil. After the coating dried, it was rolled and cut into specified electrode sizes to obtain a positive electrode with a positive electrode slurry layer formed on both sides of the positive electrode current collector. It should be noted that the unit area weight of the positive electrode slurry layer is 340 g / m². 2 .
[0083] [Making the negative electrode]
[0084] As the negative electrode active material, a mixture of graphite and SiC in a mass ratio of 65:35 is used. The negative electrode active material, montmorillonite, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) are mixed in a solid component mass ratio of 100:1:1:1, with an appropriate amount of water added to prepare a negative electrode slurry. This negative electrode slurry is coated onto both sides of a negative electrode current collector formed from copper foil. After the coating is dried, it is rolled and cut into specified electrode sizes to obtain a negative electrode with negative electrode slurry layers formed on both sides of the negative electrode current collector. It should be noted that the total mass of silicon in the silicon-containing material is 21% of the mass of the prepared negative electrode slurry layer.
[0085] [Preparation of non-aqueous electrolytes]
[0086] Ethyl carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 20:5:75. A non-aqueous electrolyte (non-aqueous solution) was prepared by dissolving lithium hexafluorophosphate (LiPF6) in this mixed solvent at a concentration of 1.3 mol / L.
[0087] [Preparation of the experimental battery cell (non-aqueous electrolyte secondary battery)]
[0088] An aluminum lead is installed on a portion of the positive electrode, and a nickel lead is installed on a portion of the negative electrode. The positive and negative electrodes are wound into a spiral shape with a polyolefin separator in between, thus creating a wound electrode body. Insulating plates are placed above and below the electrode body, and the electrode body is housed in an outer can. The negative electrode lead is soldered to the bottom of the bottomed cylindrical outer can, and the positive electrode lead is soldered to a sealing body. Electrolyte is injected into the outer can, and the opening of the outer can is sealed using a gasket through the sealing body, thereby creating a non-aqueous electrolyte secondary battery as a test battery unit.
[0089] <Experimental Battery Unit B>
[0090] In the preparation of the positive electrode active material, no sodium lauryl sulfate was added, and no carbonaceous film was formed on the surface of the positive electrode active material. In the preparation of the negative electrode, no montmorillonite was used, so that the negative electrode mixture layer did not contain montmorillonite. Otherwise, the test battery cell B was obtained in the same manner as test battery cell A.
[0091] <Experimental Battery Cell C>
[0092] In the preparation of the positive electrode active material, no sodium lauryl sulfate was added and no carbon film was formed on the surface of the positive electrode active material. Otherwise, the test battery cell C was obtained in the same manner as the test battery cell A.
[0093] <Experimental Battery Unit D>
[0094] In the fabrication of the negative electrode, montmorillonite was not used, and the negative electrode binder layer was free of montmorillonite. Otherwise, the same experimental cell cell A was obtained.
[0095] Evaluation of DC resistance (DCIR)
[0096] For the test battery cells A to D, they were charged at a constant current of 0.05C at a temperature of 25°C until they reached a constant state of charge (SOC). Then, they were left to stand for 3 hours, and the resistance value was calculated based on the voltage difference before and after charging at a current of 0.5C for 10 seconds, which was used as the DCIR.
[0097] Table 1 shows the evaluation results of DCIR for test battery cells A to D when the SOC is set to 30%. Table 2 shows the evaluation results of DCIR for test battery cells A to D when the SOC is set to 70%. Table 3 shows the evaluation results of DCIR for test battery cells A to D when the SOC is set to 90%. It should be noted that the DCIR evaluation results in Tables 1 to 3 show the difference in DCIR compared to test battery cell B (reference).
[0098] [Table 1]
[0099]
[0100] [Table 2]
[0101]
[0102] [Table 3]
[0103]
[0104] In any of Tables 1-3, the DCIR of test cell A is lower than that of any of test cells B-D. Furthermore, the difference in DCIR between test cell A and the reference is greater than the sum of the differences in DCIR between test cell C and the reference, and the differences in DCIR between test cell D and the reference.
[0105] The mechanism by which the DCIR reduction effect in battery cell A of the experiment is speculated to be as follows.
[0106] Test cell A has a Na-containing carbonaceous coating formed on the surface of the positive electrode active material. Therefore, compared to test cells B and C, which do not have this carbonaceous coating, the surface resistance of the positive electrode active material is reduced. Consequently, lithium ions are more easily released from the positive electrode active material during charging, resulting in lower reaction resistance. Furthermore, in addition to forming a Na-containing carbonaceous coating on the surface of the positive electrode active material, the negative electrode binder layer also contains montmorillonite (a silicate compound). Therefore, compared to test cells B and D, which do not contain montmorillonite (a silicate compound) in their negative electrode binder layer, the surface reaction resistance of the negative electrode active material is reduced. This silicate compound can temporarily receive lithium ions released from the positive electrode active material during charging. Therefore, the lithium ions received by the silicate compound are not retained on the surface of the negative electrode active material containing the silicon material, but are instead absorbed and stored on the surface of the negative electrode active material. Therefore, it is speculated that the DCIR of test battery cell A is lower than that of any of the test battery cells B to D, and the difference between the DCIR of test battery cell A and the reference is greater than the sum of the differences between the DCIR of test battery cell C and the reference and the differences between the DCIR of test battery cell D and the reference.
[0107] On the other hand, it is believed that test cell C, due to the presence of montmorillonite (a silicate compound) in the negative electrode mixture layer, achieves a reduction in the surface resistance of the negative electrode active material, which is attributed to the presence of montmorillonite (a silicate compound) in the negative electrode mixture layer. However, since a Na-containing carbonaceous coating is not formed on the surface of the positive electrode active material, this reduction in surface resistance is not achieved. Therefore, it is speculated that the DCIR of test cell C is lower than that of the reference test cell B, but not lower than that of test cell A.
[0108] Furthermore, while test cell D exhibits the effect of reduced reaction resistance on the surface of the positive electrode active material due to the formation of a Na-containing carbonaceous coating, the negative electrode additive layer lacks montmorillonite (a silicate compound). Consequently, lithium ions released from the positive electrode active material during charging remain trapped on the surface of the silicon-containing negative electrode active material. Therefore, it is speculated that the DCIR of test cell D is lower than that of the reference test cell B, but not lower than that of test cell A.
[0109] Therefore, it can be seen that by forming a carbonaceous coating containing one or more elements selected from the group consisting of alkali metals and alkaline earth metals other than Li on the surface of the positive electrode active material, and by making the negative electrode compound layer contain a negative electrode active material and a silicate compound, wherein the negative electrode active material contains silicon-containing materials, it is possible to specifically reduce DCIR during charging.
[0110] This disclosure is further illustrated by the following embodiments.
[0111] Component 1:
[0112] A non-aqueous electrolyte secondary battery comprises: an electrode body including a positive electrode and a negative electrode, and a non-aqueous electrolyte.
[0113] The positive electrode comprises: a positive current collector and a positive electrode flux layer formed on the surface of the positive current collector.
[0114] The negative electrode comprises: a negative electrode current collector and a negative electrode flux layer formed on the surface of the negative electrode current collector.
[0115] The positive electrode mixture layer contains positive electrode active materials.
[0116] A carbonaceous coating is formed on the surface of the positive electrode active material, and the carbonaceous coating contains one or more elements selected from the group consisting of alkali metals other than Li and alkaline earth metals.
[0117] The negative electrode mixture layer comprises a negative electrode active material and a silicate compound, wherein the negative electrode active material comprises a silicon-containing material.
[0118] Composition 2:
[0119] According to the non-aqueous electrolyte secondary battery of configuration 1, the ratio of the total mass of silicon elements contained in the silicon-containing material to the mass of the negative electrode binder layer is 20% by mass or more.
[0120] Composition 3:
[0121] According to the non-aqueous electrolyte secondary battery described in 1 or 2, the ratio of the total mass of silicon elements contained in the silicon-containing material to the mass of the negative electrode binder layer is less than 50% by mass.
[0122] Composition 4:
[0123] According to the non-aqueous electrolyte secondary battery as described in 1 or 2, the ratio of the total mass of silicon elements contained in the silicon-containing material to the mass of the negative electrode binder layer is less than 40% by mass.
[0124] Component 5:
[0125] According to any one of 1 to 4, the non-aqueous electrolyte secondary battery comprises an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase.
[0126] Composition 6:
[0127] According to the non-aqueous electrolyte secondary battery of configuration 5, the ion-conducting phase is at least one selected from the group consisting of silicate phase, carbon phase, silicide phase and silicon oxide phase.
[0128] Composition 7:
[0129] According to any one of the non-aqueous electrolyte secondary batteries comprising 1 to 6, wherein the silicate compound comprises montmorillonite.
[0130] Composition 8:
[0131] According to any one of the non-aqueous electrolyte secondary batteries comprising 1 to 7, the unit area weight of the positive electrode compound layer is 280 g / m². 2 above.
[0132] Composition 9:
[0133] According to any one of the non-aqueous electrolyte secondary batteries comprising 1 to 8, wherein the carbon coating further contains S.
[0134] Composition 10:
[0135] According to any one of the non-aqueous electrolyte secondary batteries comprising 1 to 9, wherein the carbonaceous coating contains at least one of Na and K.
[0136] Explanation of reference numerals in the attached figures
[0137] 10 Secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer casing, 17 Sealing body, 18, 19 Insulating plate, 20 Positive lead, 21 Negative lead, 22 Groove section, 23 Internal terminal block, 24 Lower valve body, 25 Insulating component, 26 Upper valve body, 27 Cover, 28 Gasket, 30 Base layer, 31 Tetrahedral layer, 32 Octahedral layer
Claims
1. A non-aqueous electrolyte secondary battery, comprising: an electrode body including a positive electrode and a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises: a positive current collector and a positive electrode flux layer formed on the surface of the positive current collector. The negative electrode comprises: a negative electrode current collector and a negative electrode flux layer formed on the surface of the negative electrode current collector. The positive electrode mixture layer contains positive electrode active materials. A carbonaceous coating is formed on the surface of the positive electrode active material, and the carbonaceous coating contains one or more elements selected from the group consisting of alkali metals other than Li and alkaline earth metals. The negative electrode mixture layer comprises a negative electrode active material and a silicate compound, wherein the negative electrode active material comprises a silicon-containing material.
2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode binder layer is 20% or more by mass.
3. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode binder layer is less than 50% by mass.
4. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The ratio of the total mass of silicon in the silicon-containing material to the mass of the negative electrode binder layer is less than 40% by mass.
5. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The silicon-containing material comprises an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase.
6. The non-aqueous electrolyte secondary battery according to claim 5, wherein, The ion-conducting phase is selected from at least one group consisting of silicate phase, carbon phase, silicide phase and silicon oxide phase.
7. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The silicate compound contains montmorillonite.
8. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The unit area weight of the positive electrode mixture layer is 280g / m². 2 above.
9. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The carbonaceous coating also contains sulfur (S).
10. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The carbonaceous coating contains at least one of Na and K.
Citation Information
Patent Citations
Positive electrode active material and nonaqueous electrolyte secondary battery
WO2023203952A1